PELATIAN PEMBUATAN SILASE KOMPLIT GUNA DI DESA DUMDUM TAOLAS (TIOWOR) KECAMATAN KAO TELUK KABUPATEN HALMAHERA UTARA - Nur Sjafani; M Ade Salim (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Community Service Activities aim to build the livestock community to be independent, increase their knowledge and skills in providing quality feed for their livestock needs. The solutions offered are through several methods : taking an approach to understand the partner group’s problems and carrying out counseling and training. As a result of service activities, partner group members can know how to feed and can make complete silage. The evaluation results show that the partner group succeeded in making complete silage